Chimeric Antigen Receptor T Cells Targeting Integrin αvβ6 Expressed on Cholangiocarcinoma Cells - Phanthaphol, Nattaporn; Somboonpatarakun, Chalermchai; Suwanchiwasiri, Kwanpirom; Chieochansin, Thaweesak; Sujjitjoon, Jatuporn; Wongkham, Sopit; Maher, John; Junking, Mutita; Yenchitsomanus, Pa-thai (Frontiers in Oncology, 2021)
Cholangiocarcinoma (CCA) is a lethal bile duct cancer that responds poorly to current standard treatments. A new therapeutic approach is, therefore, urgently needed. Adoptive T cell transfer using chimeric antigen receptor (CAR) T cells is a new therapeutic modality with demonstrated efficacy in hematologic malignancies. However, its efficacy against solid tumors is modest, and further intensive investigation continues. An important factor that influences the success of CAR T cell therapy is the selection of a target antigen that is highly expressed on cancer cells, but markedly less so in normal cells. Integrin αvβ6 is upregulated in several solid tumors, but is minimally expressed in normal epithelial cells, which suggests integrin αvβ6 as an attractive target antigen for CAR T cell immunotherapy in CCA. We investigated integrin αvβ6 expression in pathological tissue samples from patients with liver fluke-associated CCA. We then created CAR T cells targeting integrin αvβ6 and evaluated their anti-tumor activities against CCA cells. We found overexpression of the integrin αvβ6 protein in 23 of 30 (73.3%) CCA patient tissue samples. Significant association between high integrin αvβ6 expression and short survival time (p=0.043) was also observed. Lentiviral constructs were engineered to encode CARs containing an integrin αvβ6-binding peptide (A20) derived from foot-and-mouth disease virus fused with a second-generation CD28/CD3ζ signaling domain (A20-2G CAR) or with a fourth-generation CD28/4-1BB/CD27/CD3ζ signaling domain (A20-4G CAR). The A20-2G and A20-4G CARs were highly expressed in primary human T cells transduced with the engineered lentiviruses, and they exhibited high levels of cytotoxicity against integrin αvβ6-positive CCA cells (p<0.05). Interestingly, the A20-2G and A20-4G CAR T cells displayed anti-tumor function against integrin αvβ6-positive CCA tumor spheroids (p<0.05). Upon specific antigen recognition, A20-4G CAR T cells produced a slightly lower level of IFN-γ, but exhibited higher proliferation than A20-2G CAR T cells. Thus, the A20-4G CAR T cells with lower level of cytokine production, but with higher proliferation represents a promising potential adoptive T cell therapy for integrin αvβ6-positive CCA.